P787 Impact of inflammatory bowel disease on working life: A French nationwide survey. (16th January 2018) - Gonzalez, F; Buisson, A; Olympie, A; Ravel, M -H; Bienenfeld, C; Peyrin-Biroulet, L
Abstract: Background: Inflammatory bowel diseases (IBD) are chronic disabling conditions with a profound impact on social and professional life of patients. The French National IBD Patient Association "AFA" (Association François Aupetit) conducted the first nationwide survey to assess the impact of IBD on working life of patients. Methods: A qualitative phase (12 face-to-face interviews) identified relevant questions, followed by a quantitative online survey, performed from March to April 2016, targeting both AFA and non-AFA affiliated adult patients, working or having worked previously. Results: Data from 1410 IBD French patients were analysed: 1126 working, 60% AFA affiliated, 76% women, mean age 38.4 years (18+), 62% Crohn disease, 35% ulcerative colitis, 51% diagnosed for over 10 years, 27% with severe IBD and 53% with moderate IBD. Patients seek job security, but are less likely to have full-time employment: They have a higher rate of permanent work contracts (82% vs. 74%) and of public employment (36% vs. 29%) than in the general population, but a higher rate of part-time contracts (26% vs. 19%). IBD impacts professional life: 76% are satisfied with their job ; 80% of the unsatisfied patients claim it is due to IBD, 39% reported that IBD changed their career choices at the beginning or later. Only 19% declare IBD had no impact on their professional-life, while 50% claim IBD made it difficult. Highly graduated patients were less likely to reach high qualified jobs compare to the general population with same diploma (39% vs.64%). Symptoms: Fatigue is the most frequent (41%) followed by diarrhoea (25%) and fecal incontinence (18%). Communication: 89% of the patients shared their diagnosis with their colleagues, manager or health physician, mainly to justify their frequent sick leaves. The reaction was mostly supportive. However, some experienced a negative reaction from their hierarchy (18%) or colleagues (21%). 25% regretted having talked about their IBD at work. Conclusions: This is the first survey on the impact of IBD on professional life of patients. Overall, IBD had a strong negative impact on professional life. While work satisfaction remains high, IBD affects career choices, evolution, and recruitment. It restricts the access to upper socio-professional categories. Fatigue is the most disabling symptom at work. This issue is under-recognised by national stakeholders and should be systematically investigated by companies to develop adapted measures.